Metode Reduksi ISO Image Sistem Operasi Open Source Berbasis Linux - Suryana, Nana; Rosiyadi, Didi (INKOM Journal, 2012)
In this paper, the Reduction Method of ISO image for Operating System of Linux Distro (Open Source Based on Linux) is proposed. IGOS Nusantara as a Linux Distro is used on this study. The reduction method of ISO image for IGOS Nusantara consists of modules elimination and usage of an optimal compression technique. Using the reduction method optimally on the rpm files of the application packages of IGOS Nusantara will decrease their sizes. Experiment results demonstrate that some of the rpm files can be reduced from 40 MB to 29 MB. All reduced rpm files and other modules are processed into ISO image. By this method, the original size 890 MB of ISO image can be shrinked into 685 MB. The small and compact size of ISO image are very useful to save the internet bandwidth in downloading IGOS Nusantara and also to make it more responsive when it is used by users.